Thermodynamic analysis and comparison of downdraft gasifiers integrated with gas turbine, spark and compression ignition engines for distributed power generation - Mendiburu, Andres Z. [UNESP]; Roberts, Justo J. [UNESP]; Carvalho, Joao A. [UNESP]; Silveira, Jose L. [UNESP] (Elsevier B.V., 2014)
The objective of the present article is to assess and compare the performance of electricity generation systems integrated with downdraft biomass gasifiers for distributed power generation. A model for estimating the electric power generation of internal combustion engines and gas turbines powered by syngas was developed. First, the model determines the syngas composition and the lower heating value; and second, these data are used to evaluate power generation in Otto, Diesel, and Brayton cycles. Four synthesis gas compositions were tested for gasification with: air; pure oxygen; 60% oxygen with 40% steam; and 60% air with 40% steam. The results show a maximum power ratio of 0.567 kWh/Nm(3) for the gas turbine system, 0.647 kWh/Nm(3) for the compression ignition engine, and 0.775 kWh/Nm(3) for the spark-ignition engine while running on synthesis gas which was produced using pure oxygen as gasification agent. When these three systems run on synthesis gas produced using atmospheric air as gasification agent, the maximum power ratios were 0.274 kWh/Nm(3) for the gas turbine system, 0.302 kWh/Nm(3) for CIE, and 0.282 kWh/Nm(3) for SIE. The relationship between power output and synthesis gas flow variations is presented as is the dependence of efficiency on compression ratios. Since the maximum attainable power ratio of CIE is higher than that of SIE for gasification with air, more research should be performed on utilization of synthesis gas in CIE. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Gasification; Engines; Gas turbines; Power generation; Comparison